Increased Odds of Incident Alzheimer's Disease and Related Dementias in Presence of Common Non-Cancer Chronic Pain Conditions in Appalachian Older Adults. (March 2022) - Khalid, Sumaira; Sambamoorthi, Usha; Umer, Amna; Lilly, Christa L.; Gross, Diane K.; Innes, Kim E.
Background: There is a growing concern regarding the increasing prevalence of common non-cancer chronic pain conditions (NCPCs) and their possible association with Alzheimer's disease and related dementias (ADRD). However, large population-based studies are limited, especially in Appalachian and other predominantly rural, underserved populations who suffer elevated prevalence of both NCPCs and known ADRD risk factors. Objectives: We investigated the relation of NCPC to risk of incident ADRD in older Appalachian Medicare beneficiaries and explored the potential mediating effects of mood and sleep disorders. Methods: Using a retrospective cohort design, we assessed the overall and cumulative association of common diagnosed NCPCs at baseline to incident ADRD in 161, 573 elders ≥65 years, Medicare fee-for-service enrollees, 2013–2015. NCPCs and ADRD were ascertained using claims data. Additional competing risk for death analyses accounted for potential survival bias. Main Findings: Presence of any NCPC at baseline was associated with significantly increased odds for incident ADRD after adjustment for covariates [adjusted odds ratio (AOR) = 1.26 (1.20, 1.32), p < .0001]. The magnitude and strength of this association increased significantly with rising burden of NCPCs at baseline [AOR for ≥4 vs. no NCPC = 1.65 (1.34, 2.03), p -trend = .01]. The addition of depression and anxiety, but not sleep disorders, modestly attenuated these associations [AORs for any NCPC and ≥4 NCPCs, respectively = 1.16 (1.10, 1.22) and 1.39 (1.13, 1.71)], suggesting a partial mediating role of mood impairment. Sensitivity analyses, multinomial logistic regressions accounting for risk of death, yielded comparable findings. Conclusion: In this large cohort of older Appalachian Medicare beneficiaries, baseline NCPCs showed a strong, positive, dose–response relationship to odds for incident ADRD; this association appeared partially mediated by depression and anxiety. Further longitudinal research in this and other high-risk, rural populations are needed to evaluate the causal relation between NCPC and ADRD.